Model-based control of enzyme yield in solid-state fermentation - Bück, A.; Casciatori, F. P. [UNESP]; Thoméo, J. C. [UNESP]; Tsotsas, E. (My University, 2015)
Solid-state fermentation is gaining increasing importance for the production of high-added value products, for instance enzymes, from agro-industrial by-products. The main difficulty in operating this process in packed-bed bioreactors is the development of temperature and moisture gradients along the reactor length which decrease the overall productivity. In this work a practically relevant feedback control scheme is developed that allows influencing and equalizing the moisture and temperature distributions along the packed-bed bioreactor during solid-state fermentation. This prevents locally critical process conditions which may necessitate the shutdown of the operation of the bioreactor.
Keywords: distributed parameter system; drying; feedback control; heat and mass transfer; solid-state fermentation